Maggie Moore(s) [videorecording (DVD)] - Bernbaum, Paul, 1957-; Hamm, Jon, 1971-; Fey, Tina, 1970-; Stock, Micah; Mohammed, Nick; Anderson, Happy (Screen Media, 2023)
The movie takes place in a dusty desert town where nothing ever happens, as a police chief is suddenly faced with the back-to-back murders of two women with the same name.